New-onset seizure in HIV-infected adult Zambians: A search for causes and consequences. (31st January 2017) - Siddiqi, Omar K.; Elafros, Melissa A.; Bositis, Christopher M.; Koralnik, Igor J.; Theodore, William H.; Okulicz, Jason F.; Kalungwana, Lisa; Potchen, Michael J.; Sikazwe, Izukanji; Birbeck, Gretchen L.
Abstract : Objective: To identify the etiology of new-onset seizure in HIV-infected Zambian adults and identify risk factors for seizure recurrence. Methods: A prospective cohort study enrolling HIV-infected adults with new-onset seizure within 2 weeks of index seizure obtained clinical, laboratory, and neuroimaging data to determine seizure etiology. Participants were followed to identify risk factors for seizure recurrence. Risk factors for mortality were examined as mortality rates were unexpectedly high. Results: Eighty-one patients with CSF for analysis were enrolled and followed for a median of 306 days (interquartile range 61–636). Most (91%) were at WHO stage III/IV and 66 (81%) had a pre-seizure Karnofsky score ≥50. Prolonged or multiple seizures occurred in 46 (57%), including 12 (15%) with status epilepticus . Seizure etiologies included CNS opportunistic infections (OI) in 21 (26%), hyponatremia in 23 (28%), and other infections in 8 (10%). OIs included Cryptococcus (17%), JC virus (7%) and 5% each for tuberculosis, cytomegalovirus, and varicella-zoster virus. No etiology could be identified in 16 (20%). Thirty (37%) patients died during follow-up and 20 (25%) had recurrent seizures with survival being the only identifiable risk factor. Conclusions: HIV-infected adults with new-onset seizure in Zambia often have advanced HIV disease with OI being the most frequent seizure etiology. Seizure recurrence is common but no risk factors for recurrence other than survival were identified. These findings suggest an urgent need for immune reconstitution in this population. Initiating treatment for seizure prophylaxis where only enzyme-inducing antiepileptic medications are available could threaten antiretroviral efficacy.